A survey of 20-year-old Japanese women: how is their intention to undergo cervical cancer screening associated with their childhood HPV vaccination status?. Issue 2 (1st February 2021) - Kakubari, Reisa; Egawa-Takata, Tomomi; Ueda, Yutaka; Tanaka, Yusuke; Yagi, Asami; Morimoto, Akiko; Terai, Yoshito; Ohmichi, Masahide; Ichimura, Tomoyuki; Sumi, Toshiyuki; Murata, Hiromi; Okada, Hidetaka; et al.
ABSTRACT: Introduction: In Japan, two groups of women, HPV vaccinated and unvaccinated, are approaching age 20, when they should begin cervical cancer screening. To improve Japan's current poor cervical cancer screening rate, we need to know how these women are thinking about screening. Methods: We conducted an internet survey of 20-y-old women, exploring their understanding of HPV and cervical cancer screening. We then gave them leaflets with basic information about HPV and cervical cancer, stressing the importance of early detection by screening. We analyzed the leaflet's effects on their attitudes based on their vaccination status. Results: Our study of 618 women found a significantly higher intention for engagement for cervical cancer screening in women HPV-vaccinated as teenagers (29% versus 17%). They were also more aware that: (1) HPV is transmitted by sexual intercourse (49.1% versus 39.2%); (2) the HPV vaccine prevents cervical cancer (49.0% to 34.0%); and (3) the appropriate cervical cancer screening interval is every 2 y (63.3% versus 56.2%). Women in both groups responded well to the leaflet, with significant improvements in intention to receive screening. However, 65%-67% were not swayed. Discussion: HPV-vaccinated women were more knowledgeable about cervical cancer and had a greater intention to receive screening. Our educational leaflet was moderately effective in both groups for increasing intentions to screen, but the majority in both groups were still resistant to screening. Conclusion: Japan needs to develop more effective educational programs and tools to vigorously impart the importance of cervical cancer screening.